2017
DOI: 10.1192/bjp.bp.115.179093
|View full text |Cite
|
Sign up to set email alerts
|

The evidence–practice gap in specialist mental healthcare: Systematic review and meta-analysis of guideline implementation studies

Abstract: Guideline implementation does not seem to have an impact on provider performance, nonetheless it may influence patient outcomes positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 37 publications
0
52
0
7
Order By: Relevance
“…Individual factors such as personal preferences, comorbidity, concurrent medications and previous experience with medication will have an impact on the choices made. Although guidelines and algorithms in mental healthcare can improve the quality of medication use,11 12 CPGs are not always used in practice64–66 and implementation strategies do not always result in improved adherence to guideline recommendations 67. In the Recovery After an Initial Schizophrenia Episode (RAISE) study, the authors identified 39% of the sample who could have benefited from a medication review because prescribing practices were not in line with current guidelines in the USA 68.…”
Section: Discussionmentioning
confidence: 99%
“…Individual factors such as personal preferences, comorbidity, concurrent medications and previous experience with medication will have an impact on the choices made. Although guidelines and algorithms in mental healthcare can improve the quality of medication use,11 12 CPGs are not always used in practice64–66 and implementation strategies do not always result in improved adherence to guideline recommendations 67. In the Recovery After an Initial Schizophrenia Episode (RAISE) study, the authors identified 39% of the sample who could have benefited from a medication review because prescribing practices were not in line with current guidelines in the USA 68.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been postulated that a "weak" variant of the phenomenological position is adopted in the daily routine of the clinic (Parnas et al, 2011), that is, although implicitly, experienced clinicians would use several phenomenological assumptions in the elaboration of their diagnostics and proposals of treatment. Faced with the distance between the positivist explanatory models and their clinical practice (Morley, 2002) and the observation of a considerable gap between their clinical application and the treatment guidelines from neurobiological psychiatry (Girlanda et al, 2017), many precepts of a phenomenological nature are put into practice daily, albeit in an unintentional or unknowing way (Parnas et al, 2011).…”
Section: Elements Of a Psychiatric Praxis Of Phenomenological Orientamentioning
confidence: 99%
“…What effects do guideline dissemination and implementation strategies have on process and patient outcomes, i.e., on clinician behaviour and treatment outcome at the patient level? A number of papers have investigated the effects of mental health guidelines being implemented, and the results suggest that: (a) if any effects on provider performance or patient outcome are mostly moderate and temporary; (b) studies with positive outcomes used complex multifaceted strategies or specific psychological methods to implement guidelines; (c) our current knowledge about how guidelines should be implemented is sparse and inconclusive in mental health care; (d) future studies should attempt to employ more rigorous designs; (e) research on guideline implementation strategies should take into account potential barriers to knowledge translation; and (f) randomised controlled trials, controlled clinical trials and before-and-after studies comparing guideline implementation strategies v. usual care have not shown consistent positive effects of guideline implementation on provider performance, but a more consistent small to modest positive effect on patient outcomes (Weinmann et al 2007;Girlanda et al 2013Girlanda et al , 2016. This latter finding suggests that guideline implementation strategies may have affected aspects of clinician behaviour that were not measured in controlled trials and that effects on patient outcome may have come about through mechanisms that have hitherto escaped the attention of researchers.…”
Section: Guidelines and Guideline Implementationmentioning
confidence: 99%